Arterial Stiffness Increases Over Time in Relation to Lung Diffusion Capacity: A Longitudinal Observation Study in COPD - Roeder, Maurice (Int J Chron Obstruct Pulmon Dis, 2020)
BACKGROUND: Cardiovascular events are, after cancer, the most common cause of death in COPD patients. Arterial stiffness is an independent predictor of all-cause mortality and cardiovascular events. Several cross-sectional studies have confirmed increased arterial stiffness in patients with COPD. Various mechanisms in the development of arterial stiffness in COPD such as reduced lung function or systemic inflammation have been proposed. However, clinical predictors of arterial stiffness that had been reported in cross-sectional studies have not yet been confirmed in a longitudinal setting. We have assessed the course of augmentation index (AIx) - a measure of systemic arterial stiffness - and possible predictors in a cohort of COPD patients over a period of up to 7 years. METHODS: COPD patients underwent annual AIx measurement by applanation tonometry for a maximum duration of 7 years. Additionally, we performed annual assessments of lung function, blood gases, systemic inflammation, serum lipids and blood pressure. Associations between the course of AIx and potential predictors were investigated through a mixed effect model. RESULTS: Seventy-six patients (mean (SD) age 62.4 (7.1), male 67%) were included. The AIx showed a significant annual increase of 0.91% (95% CI 0.21/1.60) adjusted for baseline. The change in diffusion capacity (DLco), low-density lipoprotein (LDL), and high-sensitivity c-reactive protein (hsCRP) was independently associated with the increasing evolution of AIx (Coef. - 0.10, p<0.001, Coef. 1.37, p=0.003, and Coef. 0.07, p=0.033, respectively). CONCLUSION: This study demonstrated a meaningful increase in arterial stiffness in COPD over time. A greater annual increase in arterial stiffness was associated with the severity of emphysema (measured by DLco), systemic inflammation, and dyslipidaemia. CLINICAL TRIAL REGISTRATION: www.ClinicalTrials.gov, NCT01527773.